Respuestas

2013-09-17T03:58:26+02:00
Aplicamos la siguiente propiedad: Si  A.B=0  ------>  A=0   v    B=0

Entonces en las ecuaciones:
(x-11)²=(x-11)(x-11)=0 ------>  (x-11)=0    v    (x-11)=0
                                              x=11     v    x = 11        Soluciones iguales; C.s.={11}

(2x+1)(x+5)=0  ------->  2x+1=0     v    x+5=0
                                    x=-1/2    v     x = -5             C.s.= {-5; -1/2}

2x(x-4)(x+8)=0 ------> x(x-4)(x+8)=0 ---->  x=0    v   x-4=0  v   x+8=0
                                                           x=0    v    x=4   v     x=-8     C.s.={-8; 0; 4}

(x-1/3)(x+1/2)(x+1/6)=0  ---->  x-1/3=0  v  x+1/2=0  v  x+1/6=0
                                             x=1/3   v  x=-1/2   v    x=-1/6       C.s.={-1/2; -1/6; 1/3}